Illness (self) management, clinical and functional recovery as determinants of personal recovery in people with severe mental illnesses: A mediation analysis. - Bert-Jan Roosenschoon; Mathijs L Deen; Jaap van Weeghel; Astrid M Kamperman; Cornelis L Mulder (PLoS ONE)
This study analyzed the association between changes over time in illness self-management skills and personal recovery in patients with schizophrenia and other severe mental illnesses and determined the degree to which this association was mediated by changes in clinical and functional recovery. The rationale for the hypothesized directions of association and mediation originated from a recent randomized controlled trial (RCT) on Illness Management and Recovery (IMR), the relations between these concepts suggested in a conceptual framework of IMR, and from the results of three meta-analyses. Moreover, earlier studies indicated the relevance of examining personal recovery as an outcome for people with severe mental illnesses. Outpatient participants' data were used in this RCT (N = 165). Difference scores were constructed for all concepts by subtracting scores measured at baseline (T1) from scores at follow-up measurement (T3). We used mediation analysis to describe pathways between changes in illness management (assessed using the Illness Management and Recovery scale client version) and changes in personal recovery (assessed using the Mental-Health Recovery Measure), mediated by changes in clinical (assessed using the Brief Symptom Inventory) and functional recovery (assessed using the Social Functioning Scale). We applied the baseline data of all concepts as covariates. As inferential tests to determine the significance of the indirect paths, confidence intervals were constructed using bootstrap techniques. The results showed that the improvement in overall illness management was directly associated with improvements in personal recovery (B = .30), and indirectly through improvements in clinical recovery (indirect effect = .13) and functional recovery (indirect effect = .08). The main conclusion is that self-reported illness management appears to be more strongly and directly associated with personal recovery than indirectly via clinical and functional recovery. This analysis supports the relevance of self-management interventions such as IMR for the personal recovery of people with severe mental illnesses.